2010
DOI: 10.1111/j.1349-7006.2010.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthase inhibitor cerulenin suppresses liver metastasis of colon cancer in mice

Abstract: Fatty acid synthase (FAS) is highly expressed in many kinds of human cancers, including colorectal cancer (CRC), and we have investigated the potential use of FAS inhibitors for chemoprevention of liver metastasis of CRC in mice. Expression of FAS was evaluated in murine CRC cell lines Colon 26 and CMT 93. Cerulenin, a natural inhibitor of FAS, induced apoptosis in these cell lines. The ability of cerulenin to prevent development of liver metastatic lesions in Colon 26 was evaluated. The numbers and sizes of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 24 publications
2
59
1
11
Order By: Relevance
“…The difference in FASN expression level between OS and osteoenchondroma was significant (p<0.01). Recent studies have shown that FASN expression levels are associated with tumor cells metastasis in vivo (20,30). In our study, FASN was overexpressed in 38 of 44 patients with pulmonary metastasis, but only 48 of the 92 patients without metastasis demonstrated positive FASN expression.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The difference in FASN expression level between OS and osteoenchondroma was significant (p<0.01). Recent studies have shown that FASN expression levels are associated with tumor cells metastasis in vivo (20,30). In our study, FASN was overexpressed in 38 of 44 patients with pulmonary metastasis, but only 48 of the 92 patients without metastasis demonstrated positive FASN expression.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies revealed that the inhibition of FASN promotes apoptosis and reduces cell growth and lymph node metastasis in a mouse melanoma model (19). In Colon 26 and CMT 93 cells, FASN contributed to metastasis by upregulating the activity of the AKT pathway (20). However, the expression of FASN and the correlation between FASN and metastasis in OS is still uncertain.…”
Section: Introductionmentioning
confidence: 98%
“…, which was previously shown to repress cancer cell growth by inhibiting fatty acid synthesis (37)(38)(39)(40)(41)(42)(43). Proliferation assays were also performed using cerulenin in cells transfected with an expression vector of FASN (Fig.…”
Section: A-d)mentioning
confidence: 99%
“…Thus, FASN is considered a novel promising target for anticancer therapy. Recent studies (21,22) have revealed that FASN may also contribute to cancer cell metastasis. microRNAs (miRNAs) are endogenous small RNAs averaging 20 to 24 nucleotides, transcribed from non-protein-coding genes or introns, which mediate translational suppression or cleavage of their target mRNAs by binding to complementary sites in their 3'-UTR (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%